2019
DOI: 10.1111/dmcn.14321
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression, anxiety, and substance‐related disorders in parents of children with cerebral palsy: a systematic review

Abstract: AIM To estimate the prevalence of mental illness in parents of children with cerebral palsy (CP).METHOD This is a systematic review that follows the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols in the search for observational studies determining the prevalence of depression, anxiety, and substance abuse in parents of individuals with CP. The information sources used for this study were: PubMed, SciELO, Cochrane Library, Clinical Trials, and Biblioteca Virtual de Sa ude. RESULTS F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…Several advances in the treatment of brain and mind disorders have emerged in the past decades, [73][74][75][76][77][78][79] although there is still a need for the development and consolidation of biomarkers in psychiatry to enable further achievements in the improvement of mental health screening and diagnosis, as well as increased health care quality and a reduction in the mental health burden inherent to mental illness. 80,81 Funding. CAPES 001.…”
Section: Discussionmentioning
confidence: 99%
“…Several advances in the treatment of brain and mind disorders have emerged in the past decades, [73][74][75][76][77][78][79] although there is still a need for the development and consolidation of biomarkers in psychiatry to enable further achievements in the improvement of mental health screening and diagnosis, as well as increased health care quality and a reduction in the mental health burden inherent to mental illness. 80,81 Funding. CAPES 001.…”
Section: Discussionmentioning
confidence: 99%
“…Second, degree of disability should have been considered. Parents’ stress level often varies according to the degree of disability [ 30 , 31 ]. Therefore, a psychometric study that considers the degree of disability should be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…2 Given the 70% non-responserate in Whitney et al's study and the high rate of ADHD among non-responders in general child population studies, it is possible that ADHD rates were underestimated. 4 With regard to anxiety, however, Barreto et al seem to have only actually found one study indicating there is no presented evidence that the rate is higher than in typical children or in parents of children with other neurological disorders. 4 With regard to anxiety, however, Barreto et al seem to have only actually found one study indicating there is no presented evidence that the rate is higher than in typical children or in parents of children with other neurological disorders.…”
mentioning
confidence: 98%
“…Further, it is unclear why the authors did not include autism among the disorders that they looked for, given the high rate (18%) of autism reported by P ahlman et al 2 The systematic review by Barreto et al reports a higher prevalence of symptoms of depression and anxiety in parents of children with CP. 4 With regard to anxiety, however, Barreto et al seem to have only actually found one study indicating there is no presented evidence that the rate is higher than in typical children or in parents of children with other neurological disorders.…”
mentioning
confidence: 98%
See 1 more Smart Citation